Working Conditions of Male Construction Worker and Its Impact on Their Life: A Cross Sectional Study in Surat City - Patel, Hiteshree C; Moitra, Mohua; Mohmmed , irfan H Momin; Kantharia, S L (National Journal of Community Medicine, 2012)
Background: The construction sector is an important sector of the economy and contributes significantly to GDP. The working conditions and the facilities provided at the sites are far from satisfactory. Objective: 1) To study socio-demographic profile of male construction workers. 2) To study certain working conditions and its impact on health of workers. 3) To study the pushing factors for migration among them. Study Design: Cross-sectional. Materials and methods: Three different construction sites of Surat city were selected by convenience sampling. All male construction workers from these three sites were selected. Necessary consent and permission was obtained. Data collected in preformed, pre-tested questionnaire. Analysis was done by Epi-info software. Results: Out of 93 workers, 3.25% were children and 9.67% were adolescents. Illiteracy was 45.2%. All the workers were migrants. Skilled workers earned Rs 75 more than the unskilled workers per day. Mean hours of working was 8.5 per day. Body-ache was the commonest complaint with the average complaint being 0.8 per worker. Most common habit among them was tobacco chewing (48.38%). Morbidity was higher among unskilled workers. There was a statistically significant association between type of workers (skilled or unskilled) and morbidity status (p< 0.05).